Possible solutions of (not only) transport applications on mobile devices - Machalík, Stanislav (Univerzita Pardubice, 2017)
In this paper the basics of creation of responsive websites, online applications and information systems which can be used not only in transport are described. The main goal of responsivity lies in the correct displaying of all the content across all the types of mobile or other specific devices. A modern well-designed web application has to be able to adjust its appearance and control to the target device so that the user should not be limited by the device parameters (especially the display resolution or size) and the readability and understandability of the website content must be perfect.
Možnosti řešení (nejen) dopravních aplikací na mobilních zařízeních
Keywords: responsive web design; responzivní webdesign; fluid grid; mobile devices; flexibilní mřížka; mobilní zařízení